2020
DOI: 10.1007/s12471-020-01447-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options for patients with advanced atrial fibrillation: from lifestyle and medication to catheter and surgical ablation

Abstract: Atrial fibrillation (AF) is part of a vicious cycle that includes multiple cardiovascular risk factors and comorbidity which can promote atrial remodelling and AF progression. Most AF-related risk factors-hypertension, diabetes, sleep apnoea, obesity and sedentary lifestyle-are in essence modifiable which may prevent AF development. Treatment of associated cardiovascular conditions may prevent both symptoms and future cardiovascular events. For advanced forms of symptomatic AF refractory to lifestyle managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Mayyas et al posited that ALD antagonists may be more helpful in preventing the progression of AF than in suppressing the onset of AF; this suggests that ALD has a greater effect on AF substrate than triggers 8 . Electrical isolation of the pulmonary veins (PVI) was found to prevent AF by effectively eliminating triggers, which remains the cornerstone for ablation treatment 15 . Therefore, CPVI combined with spironolactone is expected to improve atrial fibrosis and reduce the recurrence rate of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mayyas et al posited that ALD antagonists may be more helpful in preventing the progression of AF than in suppressing the onset of AF; this suggests that ALD has a greater effect on AF substrate than triggers 8 . Electrical isolation of the pulmonary veins (PVI) was found to prevent AF by effectively eliminating triggers, which remains the cornerstone for ablation treatment 15 . Therefore, CPVI combined with spironolactone is expected to improve atrial fibrosis and reduce the recurrence rate of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Electrical isolation of the pulmonary veins (PVI) was found to prevent AF by effectively eliminating triggers, which remains the cornerstone for ablation treatment. 15 Therefore, CPVI combined with spironolactone is expected to improve atrial fibrosis and reduce the recurrence rate of atrial fibrillation. The results of this study showed a significant decrease in the inner diameter of the left atrium in Group PVI/SP (p < .001), and this diameter was smaller than in Group PVI alone (p < .05).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of approved drugs (in human therapy) targeting GPCRs is estimated to be 35-45% as there are drugs from different pharmaceutical companies that have the same goal, that is to reach the same receptor. Therefore, there are hopes that the remaining 90% of GPCRs can become a target of future drugs, especially for diseases for which there is no efficacious medication; two examples are Alzheimer's disease [2] and atrial fibrillation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%